The nexus between loan portfolio size and volatility: Does banking regulation matter? - Franziska Bremus; Melina Ludolph (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
Since the global financial crisis and the related restructuring of banking systems, bank concentration is on the rise in many countries. Consequently, bank size and its role for macroeconomic volatility (or: stability) is the subject of intense debate. This paper analyzes the effects of financial regulations on the link between bank size, as measured by the volume of the loan portfolio, and volatility. Using bank-level data for 1999 to 2014, we estimate a power law that relates bank size to the volatility of loan growth. The effect of regulation on the power law coefficient indicates whether regulation weakens or strengthens the size-volatility nexus. Our analysis reveals that more stringent capital regulation and the introduction of bank levies weaken the size-volatility nexus; in countries with more stringent capital regulation or levies in place, large banks show, ceteris paribus, lower loan portfolio volatility. Moreover, we find weak evidence that diversification guidelines weaken the link between size and volatility.
Keywords: G21; G28; E32; 330; bank size; regulation; volatility; diversification; moral hazard; power law